ECOLOGICAL ANALYSIS OF LITERATURE SHORT STORY “HARIMAU BELANG” - Nuramila Nuramila (Journal of Language, Literature and Teaching, 2020)
Nature is often not just a setting for a fictional story in a literary work, but can also be the main theme in a literary work. The existence of the link between nature and literature raises a concept of ecological problems in literature among literary critics. The term eco-criticism (ecocriticism) is used as a term regarding the concept of literary criticism related to nature and the environment. One of the writers who explored nature in literary works was Guntur Alam. One of his works is the short story "Harimau Belang". Short story "Harimau Belang" by Guntur Alam discusses ecological aspects related to the importance of protecting the forest and the importance of not behaving greedy in utilizing natural resources in the forest so that the animals in the forest can live and breed well. Based on this, the writer is interested in analyzing the short story "Harimau Belang" by Guntur Alam using literary ecological studies. This study used descriptive qualitative method. The research data were obtained using primary data and secondary data. The data analysis technique used in this research is descriptive qualitative. The technique is concretized with the ecocritical study method specifically regarding the problem of the relationships and interactions of the figures with the environment and the natural surroundings. Based on the results of the study, it was found that the natural ecology in the short story "Harimau Belang" is there is a relationship with nature as a source of human life and with efforts to preserve nature. Whereas the cultural ecology contained in the short story "Harimau Belang" is a belief in myth, mutual cooperation, and related livelihoods. Keywords: ecology, literature, short story “Harimau Belang”